Kesantunan Berbahasa Jawa di Kalangan Remaja Masyarakat Jawa di Desa Mampun Baru Pamenang Barat Merangin Jambi - Nurhayati, Nurhayati; Ngusman, Ngusman; Nursaid, Nursaid (Universitas Negeri Padang, 2013)
The purposes of this study were to described the well-manner in of Javaness language in Java teenagers in directive and expressive speech act and to described the bad-manner in Javaness language in Javaness teevagers in Desa Mampun Baru Kecamatan Pamenang Barat Kabupaten Merangin Provinsi Jambi. The data of this study is speech event in Javaness teenagers. This study was the qualitative by descriptive method. The results of this study were the Javaness teenagers in Desa Mampun Baru Kecamatan Pamenang Barat Kabupaten Merangin Provinsi Jambi pretend to used the bad-manner in speech act. There are six kind of bad-manner speech act by Javanesse teenagers, (1) appeal by force so that was unsuitable in generosity maxim, (2) suggested in rough words so that was unsuitable in tact maxim, (3) demand by force so that was unsuitable in generosity maxim, (4) compliment and gracefull in unsincerely so that was unsuitable in modesty maxim, and (6) recalled with parents in ngoko language so that was unsuitable in generosity maxim.